At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's solve for the indicated function values for the function [tex]\( g(x) = 8x + 8 \)[/tex].
a. Finding [tex]\( g(0) \)[/tex]:
To find [tex]\( g(0) \)[/tex], we substitute [tex]\( x = 0 \)[/tex] into the function:
[tex]\[ g(0) = 8(0) + 8 = 8 \][/tex]
So, [tex]\( g(0) = 8 \)[/tex].
b. Finding [tex]\( g(2) \)[/tex]:
To find [tex]\( g(2) \)[/tex], we substitute [tex]\( x = 2 \)[/tex] into the function:
[tex]\[ g(2) = 8(2) + 8 = 16 + 8 = 24 \][/tex]
So, [tex]\( g(2) = 24 \)[/tex].
c. Finding [tex]\( g\left( \frac{7}{8} \right) \)[/tex]:
To find [tex]\( g\left( \frac{7}{8} \right) \)[/tex], we substitute [tex]\( x = \frac{7}{8} \)[/tex] into the function:
[tex]\[ g\left( \frac{7}{8} \right) = 8 \left( \frac{7}{8} \right) + 8 = 7 + 8 = 15 \][/tex]
So, [tex]\( g\left( \frac{7}{8} \right) = 15 \)[/tex].
d. Finding [tex]\( g(9b) \)[/tex]:
To find [tex]\( g(9b) \)[/tex], we substitute [tex]\( x = 9b \)[/tex] into the function:
[tex]\[ g(9b) = 8(9b) + 8 = 72b + 8 \][/tex]
Evaluating this expression further, let's simplify:
[tex]\[ g(9) = 72 + 8 = 80 \][/tex]
So, [tex]\( g(9b) = 80 \)[/tex].
e. Finding [tex]\( g(b+4) \)[/tex]:
To find [tex]\( g(b+4) \)[/tex], we substitute [tex]\( x = b+4 \)[/tex] into the function:
[tex]\[ g(b+4) = 8(b + 4) + 8 = 8b + 32 + 8 = 8b + 40 \][/tex]
Evaluating this expression further, let's simplify:
[tex]\[ g(4) = 32 + 8 = 40 \][/tex]
So, [tex]\( g(b+4) = 40 \)[/tex].
In summary:
a. [tex]\( g(0) = 8 \)[/tex]
b. [tex]\( g(2) = 24 \)[/tex]
c. [tex]\( g\left( \frac{7}{8} \right) = 15 \)[/tex]
d. [tex]\( g(9) = 80 \)[/tex]
e. [tex]\( g(4) = 40 \)[/tex]
a. Finding [tex]\( g(0) \)[/tex]:
To find [tex]\( g(0) \)[/tex], we substitute [tex]\( x = 0 \)[/tex] into the function:
[tex]\[ g(0) = 8(0) + 8 = 8 \][/tex]
So, [tex]\( g(0) = 8 \)[/tex].
b. Finding [tex]\( g(2) \)[/tex]:
To find [tex]\( g(2) \)[/tex], we substitute [tex]\( x = 2 \)[/tex] into the function:
[tex]\[ g(2) = 8(2) + 8 = 16 + 8 = 24 \][/tex]
So, [tex]\( g(2) = 24 \)[/tex].
c. Finding [tex]\( g\left( \frac{7}{8} \right) \)[/tex]:
To find [tex]\( g\left( \frac{7}{8} \right) \)[/tex], we substitute [tex]\( x = \frac{7}{8} \)[/tex] into the function:
[tex]\[ g\left( \frac{7}{8} \right) = 8 \left( \frac{7}{8} \right) + 8 = 7 + 8 = 15 \][/tex]
So, [tex]\( g\left( \frac{7}{8} \right) = 15 \)[/tex].
d. Finding [tex]\( g(9b) \)[/tex]:
To find [tex]\( g(9b) \)[/tex], we substitute [tex]\( x = 9b \)[/tex] into the function:
[tex]\[ g(9b) = 8(9b) + 8 = 72b + 8 \][/tex]
Evaluating this expression further, let's simplify:
[tex]\[ g(9) = 72 + 8 = 80 \][/tex]
So, [tex]\( g(9b) = 80 \)[/tex].
e. Finding [tex]\( g(b+4) \)[/tex]:
To find [tex]\( g(b+4) \)[/tex], we substitute [tex]\( x = b+4 \)[/tex] into the function:
[tex]\[ g(b+4) = 8(b + 4) + 8 = 8b + 32 + 8 = 8b + 40 \][/tex]
Evaluating this expression further, let's simplify:
[tex]\[ g(4) = 32 + 8 = 40 \][/tex]
So, [tex]\( g(b+4) = 40 \)[/tex].
In summary:
a. [tex]\( g(0) = 8 \)[/tex]
b. [tex]\( g(2) = 24 \)[/tex]
c. [tex]\( g\left( \frac{7}{8} \right) = 15 \)[/tex]
d. [tex]\( g(9) = 80 \)[/tex]
e. [tex]\( g(4) = 40 \)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.